Evaluation of relaps in dependent inpatients - Saatçioğlu, Ömer; Yapıcı, Aslıhan; Ciğerli, Gözde; Üney, Rıdvan; Çakmak, Duran (Journal of Dependence, 2008)
Objective: Addiction is a chronic relapsing disorder. Approximately 40-50 percent of alcohol or drug dependent inpatients use again substance within six months. Determination of relaps period may simplify the relapse prevention. Method: The medical records of 113 patients who had multiple hospitalizations at AMATEM clinic in Bakırköy Research and Training Hospital for Psychiatric and Neurological Diseases were evaluated retrospectively. Sociodemographic features, characteristics of alcohol and drug dependence, life events, causes of relapse, duration of remission, withdrawal symptoms, psychiatric and physical disease history, criminal history were determined. Results: Among 113 dependents, 66 had alcohol and 47 had drug dependence. In both groups, the rate of female patients was low. Most of the patients had primary school graduated. The rates of psychiatric and physical disease history was higher. Cognitive differences were higher than other relapse determinators in alcohol dependants. The rate of coping skills failure were higher in drug dependants. Conclusion: Same or different factors will contribute to relapse in alcohol and drug dependants, even if there is some different factors in periodical life events and impact areas between both groups.